On the riverbank - Temple, Charles A., 1947-; Hall, Melanie W. (Boston : Houghton Mifflin, 1992)
Sitting on the riverbank under the yellow moon, a boy fishes for catfish with Daddy and Mama.
Publisher's Weekly
Booklist
School Library Journal
2.9
K-3
Keywords: Fishing -- Fiction; Afro-Americans -- Fiction; Stories in rhyme; Fishing -- Fiction; Stories in rhyme